Indeks Transparansi Pengelolaan Anggaran Daerah: Bagaimana Perkembangannya? - Nulailah Nulailah; Syamsul Syamsul (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
The purpose of this research is to measure the transparency of regional budget management (TPAD). This type of research is descriptive research, using documentation data collection techniques. The data analyzed is regional budget management data, which is obtained through observations on the official website of local governments in Indonesia. The results of the analysis show that the first rank of the TPAD index was achieved by the Provincial Government of West Sumatra, the second rank was occupied by the Provincial Government of Riau, and the third rank was occupied by the Provincial Government of South Kalimantan. In addition, it was also found that the average value of the TPAD index was 24.24 percent. This means that the overall level of TPAD is still classified as insufficient, in other words, the management of regional budgets in Indonesia is still very non-transparent. However, this study also shows that the TPAD index in Indonesia continues to improve from year to year.